2009
DOI: 10.1016/j.annepidem.2009.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors among Asian Americans: Results from a National Health Survey

Abstract: PURPOSE We assessed the prevalence of major cardiovascular disease (CVD) risk factors among Chinese, Asian Indian, Filipino, and other Asian populations compared to non-Hispanic Whites in the United States. METHODS We analyzed aggregated data from the National Health Interview Survey (NHIS) from 2003 to 2005. Bivariate analyses were used to determine differences in the prevalence of CVD risk factors among Asian subgroups and white adults. Logistic regression analyses were also conducted to compare each Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
150
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(166 citation statements)
references
References 24 publications
15
150
0
Order By: Relevance
“…In California, South Asian men ages 25-44 years have three times the relative risk of death from CVD in comparison to the age-matched general population [4]. Epidemiologic studies have documented that South Asian immigrants have higher prevalence of medical CVD risk factors than the general population, such as diabetes, dyslipidemia, and metabolic syndrome, possibly due to a genetic predisposition to insulin resistance and central adiposity [6,9,11,[22][23][24][25][26][27][28][29]. They also have high rates of behavioral CVD risk factors, including physical inactivity and diets low in fruits and vegetables [9, 23-25, 28, 30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…In California, South Asian men ages 25-44 years have three times the relative risk of death from CVD in comparison to the age-matched general population [4]. Epidemiologic studies have documented that South Asian immigrants have higher prevalence of medical CVD risk factors than the general population, such as diabetes, dyslipidemia, and metabolic syndrome, possibly due to a genetic predisposition to insulin resistance and central adiposity [6,9,11,[22][23][24][25][26][27][28][29]. They also have high rates of behavioral CVD risk factors, including physical inactivity and diets low in fruits and vegetables [9, 23-25, 28, 30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…3 Of particular concern are the consistently high rates of hypertension among Filipinos, the third largest Asian American population in the U.S. 4 The 2004-2006 National Health Interview Survey (NHIS) found that Filipino adults were most likely to have ever been told that they had hypertension when compared to other Asian groups, with a prevalence of 27 %. 5,6 Additionally, several regional studies conducted among Filipinos indicate that this population possesses a disproportionately higher burden of hypertension compared with whites and other Asian American groups. [7][8][9][10][11][12] According to data from the 2005-2006 National Health and Nutrition Examination (NHANES), Filipinos have a 41 % prevalence of hypertension, 3 a rate that is approaching that of black adults in the U.S. who have consistently been shown to have high BP.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other racial/ethnic groups in the U.S., Asian Indians have greater risk of obesity-related conditions, such as diabetes mellitus and coronary heart disease (Flowers et al, 2010;Holland et al, 2011;Joshi et al, 2007;Misra et al, 2010;Mohanty et al, 2005;Palaniappan et al, 2010). Physical inactivity, diets low in fruits and vegetables, and a genetic predisposition to insulin resistance and central adiposity are believed to contribute to this disparity (Daniel and Wilbur, 2011;Fernandez et al, 2011;Ghai et al, 2012;Joshi et al, 2007;Ye et al, 2009).…”
Section: Introductionmentioning
confidence: 99%